2013
DOI: 10.1029/2012jf002515
|View full text |Cite
|
Sign up to set email alerts
|

Grounding line migration and high‐resolution calving dynamics of Jakobshavn Isbræ, West Greenland

Abstract: [1] We performed three field campaigns in 2004, 2007, and 2010 at the southern margin of the Jakobshavn Isbrae, West Greenland, in order to infer flow velocities and their changes from photogrammetric time-lapse imagery with a temporal resolution of 20 min and a spatial spacing of about 30 m on the glacier surface. Area-wide analysis of more than 3000 three-dimensional trajectories at individual glacier positions allow for both the mapping of the grounding line and the detailed observation of flow variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 81 publications
6
53
0
Order By: Relevance
“…Buoyancy-driven calving is an important process on large, fast-flowing outlet glaciers [59][60][61][62][63][64]. Rapid ice flow into deep water can create 'super-buoyant' conditions, in which ice fronts are out of hydrostatic equilibrium and subject to large upward-directed torque forces (Fig.…”
Section: Processes Of Frontal Ablationmentioning
confidence: 99%
“…Buoyancy-driven calving is an important process on large, fast-flowing outlet glaciers [59][60][61][62][63][64]. Rapid ice flow into deep water can create 'super-buoyant' conditions, in which ice fronts are out of hydrostatic equilibrium and subject to large upward-directed torque forces (Fig.…”
Section: Processes Of Frontal Ablationmentioning
confidence: 99%
“…The presented approach has been developed in the course of several glacier measurement projects between 2004(e.g. Dietrich et al, 2007Rosenau et al, 2013;Schwalbe et al, 2016). This paper has the aim of integrating the experiences gained from these projects.…”
Section: Introductionmentioning
confidence: 99%
“…S6 and S7. Previous studies indicate that apart from calving events, short-term ice velocity variations at Jakobshavn Isbrae are well described with simple tidal response models (e.g., Rosenau et al, 2013;Podrasky et al, 2014). Diurnal variation caused by surface melting may also contribute to velocity variation.…”
mentioning
confidence: 99%
“…However, some basal conditions, such as grounding line position, can be inferred from measured ice motion (Heinert Riedel, 2007;Rignot et 15 al., 2011;Rosenau et al, 2013). It has been observed that for many marine-terminating glaciers, ice speed is affected by ocean tides (e.g., Makinson et al, 2012;Podrasky et al, 2014;Voytenko et al, 2015a).…”
mentioning
confidence: 99%
See 1 more Smart Citation